1991
DOI: 10.1021/ma00013a001
|View full text |Cite
|
Sign up to set email alerts
|

A chemical approach to the orbitals of organic polymers

Abstract: The electronic structure of the prototypical unsaturated and saturated organic polymers polyacetylene and polyethylene is elucidated by a building-up process starting from a linear carbon chain, which is then kinked and finally has one or two hydrogen atoms attached to it. In this process the common features as well as the differences between polyacetylene and polyethylene (semiconductor vs large band gap insulator, unsaturation vs saturation) emerge in a natural way. The emphasis is on bringing together the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 17 publications
1
70
0
Order By: Relevance
“…For these relatively thin active layers, using a constant generation rate G max throughout the active layer does not change the simulation results compared to the use of the calculated optical profile as input [34]. The slightly higher V oc of the low MW cell originates from the inversely proportional relationship between the polymer band gap and the average number of repeating units in each chain [35]. At short-circuit conditions, the average dissociation probability of bound electron-hole pairs in the high MW cell is 19% higher (relative) than in the low MW device, due to the reduction in k f .…”
Section: Resultsmentioning
confidence: 99%
“…For these relatively thin active layers, using a constant generation rate G max throughout the active layer does not change the simulation results compared to the use of the calculated optical profile as input [34]. The slightly higher V oc of the low MW cell originates from the inversely proportional relationship between the polymer band gap and the average number of repeating units in each chain [35]. At short-circuit conditions, the average dissociation probability of bound electron-hole pairs in the high MW cell is 19% higher (relative) than in the low MW device, due to the reduction in k f .…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies agree that the band gap problem is due to the derivative discontinuity in the exchange correlation functional, they come to different conclusions about whether the error is caused by too-high LUMO energies or by problems with HOMO and LUMO energies. Levy et al 2 found that the center of the DFT band gap is given correctly. Thus HOMO and LUMO have to be too high or too low by the same amount.…”
Section: Ea Ipmentioning
confidence: 98%
“…The semiconducting properties in conjugated polymers stem from the covalent interactions between the monomers on the backbone of the p-conjugated polymer 1 . Although polymer chains provide a conjugated path for charge transport, real devices offer only limited charge mobility due to the presence of disorder, which disrupts the p-conjugation, and due to polarization of the surrounding medium, which augments the effective mass of the charge carriers.…”
mentioning
confidence: 99%